Numerical Simulations in Engineering and Science - Rao, Srinivas P. (IntechOpen, 2018)
Computational science is one of the rapidly growing multidisciplinary fields. The high-performance computing capabilities are utilized to solve and understand complex problems. This book offers a detailed exposition of the numerical methods that are used in engineering and science. The chapters are arranged in such a way that the readers will be able to select the topics appropriate to their interest and need. The text features a broad array of applications of computational methods to science and technology. This book would be an interesting supplement for the practicing engineers, scientists, and graduate students.